The Influence of Korean Pop (K-Pop) Culture on Learning Motivation of Senior High School Students in Tulungagung Regency - Rahmadani, Bella Wahyu; Sunandar, Asep; Sobri, Ahmad Yusuf (Proceedings Series of Educational Studies, 2024)
The research aims are: (1) to determine level interest of senior high school students in Tulungagung Regency in Korean Pop (K-Pop) culture; (2) to determine level the learning motivation of senior high school students in Tulungagung Regency; (3) to determine the effect of the influx of K-Pop culture on the learning motivation of senior high school students in Tulungagung Regency. Research using quantitative descriptive with regression analysis technique. Sampling techniques using Simple Random Sampling were used in each school with a total sample of 187 students. Analysis techniques used are descriptive analysis techniques, prerequisite analysis tests, and hypothesis testing with Pearson Product Moment correlation through the help of IBM SPSS 20. Results of this research are: (1) the interest of senior high school students in Tulungagung Regency towards K-Pop culture is in high category; (2) the learning motivation of senior high school students in Tulungagung Regency is in high category; (3) there is a significant positive influence between K-Pop culture on the learning motivation of senior high school students in Tulungagung Regency. Keywords: K-Pop culture; learning motivation; students